2021
DOI: 10.1016/j.mcpro.2021.100089
|View full text |Cite
|
Sign up to set email alerts
|

HLA Class II Presentation Is Specifically Altered at Elevated Temperatures in the B-Lymphoblastic Cell Line JY

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…5 ). Demmers 41 . used DDA on an Orbitrap Fusion Lumos Tribrid with electron-transfer/higher-energy collision dissociation (EThcD) fragmentation, and a 90 min LC gradient.…”
Section: Resultsmentioning
confidence: 99%
“…5 ). Demmers 41 . used DDA on an Orbitrap Fusion Lumos Tribrid with electron-transfer/higher-energy collision dissociation (EThcD) fragmentation, and a 90 min LC gradient.…”
Section: Resultsmentioning
confidence: 99%
“…To expand the results obtained in the current study to other HLA-DR and -DP allotypes as well as the HLA-DQ locus, the analysis of the 5856 parental proteins containing HLA class II ligands previously reported was carried out. Up to 86% of our parental protein data set was present in the pool of these studies.…”
Section: Resultsmentioning
confidence: 99%
“…The B-lymphoblastoid cell line JY, homozygote in class I alleles (HLA-A*02:01, HLA-B*07:02, HLA-C*07:02) was cultured in RPMI 1640 supplemented with 10% fetal bovine serum, 50 U/mL penicillin, and 50 μg/mL streptomycin. HLA class I peptides were retrieved via immunoaffinity purification, as described previously ( 24 , 27 ). Specifically, HLA class I complexes were immunoprecipitated using the pan-HLA class I mouse monoclonal IgG2a antibody W6/32 ( 28 ), and antigen peptides were separated from HLA molecules by elution with 10% (v/v) acetic acid, and filtration over a 10-kDa molecular weight cutoff membrane (Merck Millipore).…”
Section: Methodsmentioning
confidence: 99%
“…Here, we first revisited the ligandome of the JY B-lymphoblastoid cell line, a model cell line used by several groups active in immunopeptidomics including ours (27,(33)(34)(35), as it has relative high expression of HLA complexes, and is homozygote in its HLA class I alleles, harbouring just HLA-A*02:01, HLA-B*07:02, and HLA-C*07:02 alleles. We have previously shown that several thousand of HLA peptides can be identified when analyzing JY cells.…”
Section: Triggered Ms Detection Of O-glcnacylated Hla Peptide Ligandsmentioning
confidence: 99%